Аналіз розвитку трансмісійних установок сучасних колісних тракторів - Кожушко, Андрій Павлович; Даниленко, Віталій Дмитрович; Селевич, Сергій Геннадійович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Проаналізовано технічні рішення світових тракторобудівників при побудові трансмісій колісних тракторів. При вирішенні поставленої мети використовувалась методика, яка передбачала аналіз трансмісій за способом трансформації крутного моменту (ступінчасті та безступінчасті) та принципом дії (механічні, гідравлічні, електричні). Як результат висвітлено моделі таких тракторобудівників як: Case IH, Claas, Deutz-Fahr, Fendt, John Deere, Massey Ferguson, New Holland, Steyr, Valtra. Практична значимість роботи полягає у надані рекомендацій щодо актуальних технологій конструювання трансмісій колісних тракторів.

The increase in the production of agricultural food products leads to the creation of energy-rich wheeled tractors, which are able to realize the power of the engine by increasing the speed of movement (productivity) or traction characteristics. But this direction of development has a counterbalance in environmental protection actions. So, in the European Union, emissions of carbon monoxide, hydrocarbons, nitrogen oxides, solid particles, etc. are limited for offroad vehicles. The outlined directions of development are of a contradictory nature, so tractor manufacturers are trying to create transmission units designed to meet the performance and environmental needs of a wheeled tractor. Therefore, the material of this article aims to analyze the technical solutions of the world's tractor manufacturers in the construction of transmissions of wheeled tractors. When solving the set goal, a technique was used, which involved analysis by the method of torque transformation (stepped and stepless) and the principle of action (mechanical, hydraulic, electric). As a result, the models of such tractor manufacturers as: Case IH, Claas, Deutz-Fahr, Fendt, John Deere, Massey Ferguson, New Holland, Steyr, Valtra were analyzed. The practical significance of the work lies in the provision of recommendations on current technologies for the construction of transmissions of wheeled tractors.
Analysis in development of transmissions for modern wheeled tractors
Keywords: колісний трактор; трансмісія; powershift; подвійне зчеплення; безступінчаста трансмісія; гібрид; електрифікація; електротрактор; wheeled tractor; transmission; double clutch; continuously variable transmission; hybrid; electrification; electric tractor